Dividends, Taxes, and Signaling: Evidence from Germany - Amihud, Yakov; Murgia, Maurizio (Journal of Finance, 1997)
The higher taxation of dividends in the United States gave rise to theories that explain why companies pay dividends. Tax-based signaling models propose that the higher tax on dividends is a necessary condition to make them informative about companies' values. In Germany, where dividends are not tax-disadvantaged and in fact are taxed lower for most investor classes, these models predict that dividends are not informative. However, we find that the stock price reaction to dividend news in Germany is similar to that found in the United States. This suggests other reasons, beyond taxation, that make dividends informative.